Please Enter Your Home Location: Geoprivacy Attitudes and Personal Location Masking Strategies of Internet Users. Issue 3 (3rd May 2020) - Seidl, Dara E.; Jankowski, Piotr; Clarke, Keith C.; Nara, Atsushi
Abstract : Location masking, or geomasking, is a practice typically undertaken by data stewards who wish to release a georeferenced data set without infringing on the privacy of those whose data are involved. With numerous opportunities to transmit our personal locations through electronic devices, individuals have the agency through masking to stem the flow of their location data or otherwise engage in obscuring their locations. Relatively little is known about the factors that influence individuals to protect their location privacy and the extent to which they do so. Joining a growing recognition of individual-level privacy efforts, this study examines the predictors of personal-level location masking and the relationships among geoprivacy-related knowledge, attitudes, and behavior. Using a probability-based sample and an open online sample from California, this study finds that in situ personal masking behavior is consistent across demographic groups. A key attitude influencing whether or not participants choose to mask location is trust in Web sites to protect their personal data. Greater knowledge about how location data are transmitted and higher concern for privacy are positively correlated with masking behavior. Key Words: geomasking, geoprivacy, obfuscation, privacy, survey .